Penerapan Augmented Taylor Rule pada Kebijakan Suku Bunga: Periode Sebelum Selama dan Pasca Krisis - Imam Awaluddin; Indah Fadhilah (CV. ITTC INDONESIA, 2026)
The COVID-19 pandemic created major economic disruption and global uncertainty, questioning the reliability of the conventional Taylor Rule in guiding monetary policy. This study aims to examine changes in Bank Indonesia’s monetary policy reaction function across three phases: before, during, and after the COVID-19 pandemic. The study applies an Augmented Taylor Rule specification incorporating the inflation gap, output gap, real effective exchange rate (REER), and the Federal Funds Rate. Using a quantitative approach, monthly macroeconomic data from November 2014 to September 2025 are obtained from Bank Indonesia, the Central Statistics Agency, and international financial databases. The sample is divided into pre-pandemic, pandemic, and post-pandemic periods. Data are analyzed using the Autoregressive Distributed Lag (ARDL) model to estimate long-run relationships and short-run dynamics. The findings indicate that monetary policy behavior varies across phases. Prior to the pandemic, the policy rate response is largely inflation-oriented with limited sensitivity to output fluctuations. During the crisis, the reaction function becomes more flexible, responding to domestic economic contraction and external pressures. In the post-pandemic period, policy gradually normalizes, although global interest rates remain relevant. Overall, the results suggest that Bank Indonesia’s policy rule is adaptive to changing macroeconomic conditions rather than structurally fixed.